Benefits of Remanufacturing in Reverse Supply Chains - Maulida Boru Butar Butar; Mohammad Yamin (Science and Technology: Recent Updates and Future Prospects Vol. 11, 2024)
This paper described an overview of a reverse supply chain in general and a re-manufacturing process in a reverse supply chain. A Reverse Supply Chain (RSC) deals with the backward flow of products returned from users. Increasing attention has been given to the RSC due to the increasing value of products and technology at the end of direct supply chains as well as the impact of green legislation. A general model was used in order to examine possible re-manufacturing processes in reverse supply chains. Several remanufacturing model processes were investigated. A case study on a small-to-medium enterprise dealing with electronic products and having RSC processes was considered. A mathematical model was proposed to evaluate the cost of remanufacturing process with the objective of minimizing remanufacturing cost. Using cost as a measurement metric in this research limits the model, as minimizing cost is not always the main objective of a system. With end-of-life products, the mathematical model could be different to cover regulation instead of minimum cost.